The integration of alien plants in mutualistic plant–hummingbird networks across the Americas: the importance of species traits and insularity. Issue 6 (14th March 2016) - Maruyama, Pietro K.; Vizentin‐Bugoni, Jeferson; Sonne, Jesper; Martín González, Ana M.; Schleuning, Matthias; Araujo, Andréa C.; Baquero, Andrea C.; Cardona, Juliana; Cardona, Paola; Cotton, Peter A.; Kohler, Glauco; Lara, Carlos; et al.
Abstract: Aim: To investigate the role of alien plants in mutualistic plant–hummingbird networks, assessing the importance of species traits, floral abundance and insularity on alien plant integration. Location: Mainland and insular Americas. Methods: We used species‐level network indices to assess the role of alien plants in 21 quantitative plant–hummingbird networks where alien plants occur. We then evaluated whether plant traits, including previous adaptations to bird pollination, and insularity predict these network roles. Additionally, for a subset of networks for which floral abundance data were available, we tested whether this relates to network roles. Finally, we tested the association between hummingbird traits and the probability of interaction with alien plants across the networks. Results: Within the 21 networks, we identified 32 alien plant species and 352 native plant species. On average, alien plant species attracted more hummingbird species (i.e. aliens had a higher degree) and had a higher proportion of interactions across their hummingbird visitors than native plants (i.e. aliens had a higher species strength). At the same time, an average alien plant was visited more exclusively by certain hummingbird species (i.e. had a higher level of complementary specialization). Large alien plants and those occurring on islands had more evenly distributed interactions, thereby acting as connectors. Other evaluated plant traits and floral abundance were unimportant predictors of network roles. Short‐billed hummingbirds had higher probability of including alien plants in their interactions than long‐billed species. Main conclusions: Once incorporated into plant‐hummingbird networks, alien plants appear strongly integrated and, thus, may have a large influence on network dynamics. Plant traits and floral abundance were generally poor predictors of how well alien species are integrated. Short‐billed hummingbirds, often characterized as functionally generalized pollinators, facilitate the integration of alien plants. Our results show that plant–hummingbird networks are open for invasion.